Soekarno’s Thought on Islamic Education - Riza Fahmi (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
Syamsul Kurniawan, et al. 2016. Pemikiran Pendidikan Islam Soekarno. Jogyakarta: Samudra Biru Publisher.Sukarno as the founding father of the Republic of Indonesia had the intellect, charisma and verbal abilities to enchant millions of Indonesians when delivering a speech. His ability of a great speech made Indonesians fall in love with the man who was born in Surabaya. Certainly not easy to make millions of people fall in love with the figure of Soekarno if he himself did not have the intelligence, skills and strong charisma. Sukarno's ideas, the history of his life to his personal life are still often described as if his figure displays an aura of attraction for writers and researchers to uncover the background of his life. Many books tell the life of Sukarno, his thought and people around him such as Cindy Adams (1982) entitled Bung Karno the speaker for the people of Indonesia, Soedjiato et al (2001) Bung Karno and Islamic discourse, Badri Yatim (1999) Soekarno; Islam and Nationalism, Maslahul Falah (2003) Islam à la Soekarno, Traces of Indonesian Liberal Islamic Thought and so forth.